Disparate Effects of Disruptive Events on Children - Florencia Torche; Jason Fletcher; Jennie E. Brand (RSF: The Russell Sage Foundation Journal of the Social Sciences, 2024)
Disruptive events such as economic recessions, natural disasters, job loss, and divorce are highly prevalent among American families. These events can have a long-lasting impact when experienced during childhood, potentially altering academic achievement, socioemotional well-being, health and development, and later life socioeconomic status. Much research has considered the overall impact of disruptive events on children’s lives, but the consequences of disruption also vary across groups. The same event may have profound negative consequences for some groups, minor or no impact for others, and even be a generative or positive turning point for other groups. This issue focuses on the disparate consequences of disruptive events on children. We consider theoretical approaches accounting for effect heterogeneity and methodological challenges in identifying unequal impacts. We also review an emerging multidisciplinary literature accounting for variation in the impact of disruption across several widely studied domains that affect children’s life chances, including economic, household, educational, health, and environmental events.